Soil : reflections on the basis of our existence - Wallander, Hakan (Springer International Publishing, 2014)
It is well known that the soil beneath our feet is one of the most critical components for life on our planet. And yet it holds secrets that would surprise even the most avid gardener. Håkan Wallander, Professor of Soil Biology at Lund University, takes us on a journey through this hidden and multifaceted world, sharing his intimate knowledge of soil acquired during years of research and visits to the rainforests of South America, Africa's deserts and North America's glaciers, interwoven with observations from his homeland, Sweden. Through words and pictures, Wallander brings to life the biological and chemical processes that shape and form the soil. He explains the critical role of bacteria and fungi in soil fertility, interspersing personal reflections with scientific argument and illuminating his subject with fascinating insights. What, for instance, makes a fine wine explode on our taste buds like an Olympic fireworks display? This is a book like no other. One that makes the soil a little easier - and infinitely more exciting - to understand.